IITA Townhall meeting with BoT and Staff_23 May 2023 - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2023)
Townhall meeting with the Board of Trustees and Staff including both outgoing, Prof. Christian Borgemeister and incoming, Roel Merckx, Board chairs at the HQ on 23 May 2023.